2020
DOI: 10.1186/s12884-020-03177-3
|View full text |Cite
|
Sign up to set email alerts
|

Twin pregnancy complicated with congenital Hemivertebra: report of two cases and literature review

Abstract: Background: Hemivertebra deformity, involving one or multiple vertebral bodies, is one of the important causes of congenital scoliosis. Congenital fetal hemivertebrae could be diagnosed by ultrasonography and confirmed by fetal magnetic resonance imaging during pregnancy. However, reports of hemivertebrae in twins during the perinatal period are very rare. Case presentation: We report two cases of congenital fetal hemivertebrae, each affecting one fetus in a dichorionic diamniotic (DCDA) twin pregnancy. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In humans, hemivertebra is a rare congenital anomaly and its incidence is estimated at 0.05%-0.1% and is more common in females (Shah et al, 2020;Varras & Akrivis, 2010;Xu et al, 2020). In animals, hemivertebra is the most common congenital malformation in dogs (De Rycke & Saunders, 2017;Ryan et al, 2017;Schlensker & Distl, 2016;Wyatt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, hemivertebra is a rare congenital anomaly and its incidence is estimated at 0.05%-0.1% and is more common in females (Shah et al, 2020;Varras & Akrivis, 2010;Xu et al, 2020). In animals, hemivertebra is the most common congenital malformation in dogs (De Rycke & Saunders, 2017;Ryan et al, 2017;Schlensker & Distl, 2016;Wyatt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Hemivertebra is one of the important causes of deviation from the normal curvature of the spine because the growth potential of the affected vertebrae is like the normal vertebrae (Yang et al, 2020). This condition can result in different structural deformities of the spinal axis including scoliosis, lordosis, and/or kyphosis (Xu et al, 2020). Structural abnormalities may affect the spinal cord so, a neurological examination should be considered to determine the neurological signs (Kaplan, Spivak, & Bendo, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, hemivertebra is a rare congenital malformation, and its incidence is estimated at 0.05%–0.1% and is more common in females (Shah et al, 2020; Varras & Akrivis, 2010; Xu et al, 2020). In animals, hemivertebra is the most common congenital malformation in dogs (De Rycke & Saunders, 2017; Ryan et al, 2017; Schlensker & Distl, 2016; Wyatt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%